TBCCO thin films and passive microwave devices - Kale, K; Jenkins, A; Jim, K; O'Connor, J; Dew-Hughes, D; Edwards, D; Bramley, A; Glassey, B; Grovenor, C; Goringe, M; Pecz, B (1996)
Thin films of Tl-based HTS have been deposited on various substrates with and without buffer layers. A variety of microwave devices have been fabricated from such films (both single side and double sided). These include planar filters and a low phase noise oscillator. Experimental results for these devices demonstrate performance enhancements over similar copper implementations of the devices.